Translational implications of circadian activity alterations in an experimental model of late-onset depression induced by prenatal excess of glucocorticoids - Spulber, Stefan; Bose, Raj; Elberling, Frederik; Conti, Mirko; Ceccatelli, Sandra (Frontiers in Behavioral Neuroscience, 2025)
Most neuropsychiatric conditions, including neurodevelopmental disorders, can have different etiology depending on genetic influences, environmental factors, and gene-environment interactions. Consistent evidence points to low birth weight, commonly associated with prenatal exposure to excess glucocorticoids (GC), as risk factor for neuropsychiatric disorders including depression, ADHD and schizophrenia. In this review we give an overview of our behavioral and mechanistic studies linking prenatal exposure to GC to depression. The behavioral analyses in our mouse model revealed that prenatal exposure to synthetic GC dexamethasone (DEX) alters hippocampal neurogenesis and induces depression-like behavior that responds differently to antidepressive therapies. Using neural progenitor cells as an in vitro experimental model, we could show changes in the methylation state of genes regulating proliferation, differentiation, and migration suggesting that epigenetic modifications are involved in neurogenesis alterations induced by GC. A particularly interesting observation was the alteration in circadian patterns of activity accompanied by weaker coupling between the central clock and peripheral oscillators preceding the late onset of depression in mice exposed to DEX in utero. The results suggest that alterations in patterns of circadian spontaneous activity may predict the onset of depression and the response to therapy in depressed patients. Our collaborative clinical investigations provide evidence for the prognostic value of circadian activity analysis in predicting the response to antidepressant treatments in patients affected by major depressive disorder.